De kunstcollectie van het bouwfonds : Bouwfonds Nederlandse Gemeenten. - Beeren, W.A.L.; Viersen, H.J.; Wijers, Louwrien (Amsterdam : Stedelijk Museum Amsterdam, 1989)
Ambar, Iene ; Anzinger, Siegfried ; Armando ; Birza, Rob ; Blais, Jean-Charles ; Buisman, Sjoerd ; Cleveland, Buster ; Commandeur, Jan ; Content, Eli ; Defesche, Pieter ; Diederen, Jef ; Dieleman, Piet ; van Elk, Ger ; Franse, Kees ; Galan, Julio ; Galis, Vera ; Gudmundsson, Sigurdur ; Hahn, Susanne ; Hattink, Adri ; Honegger, Gottfried ; Jetelova, Magdalena ; Klashorst, Peter ; Komoski, Bill ; van Koningsbruggen, Rob ; Kuipers, Michel ; Lafontaine, Marie-Jo ; Landsaat, Hans ; Lap, Geert ; Lataster, Ger ; Lucassen ; Lucebert ; Meijers, Jan ; Mol, Pieter Laurens ; Molin, Lei ; Oestreicher, Helly ; Oldenburg, Claes ; Ploeg, Maarten ; Raveel, Roger ; Roeland, Jan ; Rogge, Cornelius ; Rosenquist, James ; Sanders, Willem ; Schabracq, Alexander ; Sierhuis, Jan ; Smits, Kees ; Van Soest, Pierre ; Titus-Carmel, Gérard ; de Vaal, Elizabeth ; Veneman, Peer ; Verkerk, Emo ; Volten, André ; Vroegindeweij, Leo ; Vunderink, Ido ; van der Waerden, Anne ; Weidner, Renate ; Westerik, Co ; Yoshiya, Eko
De kunstcollectie van het bouwfonds, Bouwfonds Nederlandse Gemeenten, Stedelijk Museum Amsterdam, 10.12.1988 - 29.1.1989
Nederlands
boek